2006
DOI: 10.1289/ehp.8280
|View full text |Cite
|
Sign up to set email alerts
|

Altered Breast Development in Young Girls from an Agricultural Environment

Abstract: In several human populations, the age at which female breast development begins is reported to have declined over the last five decades. Much debate has occurred over whether this reported decline has actually occurred and what factors contribute to it. However, geographical patterns reflecting earlier developmental onset in some human populations suggest environmental factors influence this phenomenon. These factors include interactions between genetic makeup, nutrition, and possible cumulative exposure to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…We propose that embryonic exposures alter breast architecture, as supported by the discovery that pesticide-exposed girls exhibit breastdevelopment that is associated with adipose deposition and not ductal or glandular growth (208), and that adult exposures alter the initiation or progression of lactation in the same manner as endogenous Es. The limited data in humans comprise a data gap and should be the subject of further research.…”
Section: Disruptions Of the Ovarymentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that embryonic exposures alter breast architecture, as supported by the discovery that pesticide-exposed girls exhibit breastdevelopment that is associated with adipose deposition and not ductal or glandular growth (208), and that adult exposures alter the initiation or progression of lactation in the same manner as endogenous Es. The limited data in humans comprise a data gap and should be the subject of further research.…”
Section: Disruptions Of the Ovarymentioning
confidence: 99%
“…In a study examining breast development in girls exposed both in utero and lactationally to differing amounts of the flame retardant polybrominated biphenyl, there was an increased OR (2.2, 95% CI 0.5-9.8) of early breast development in girls exposed to moderate, but not high or low, concentrations of polybrominated biphenyl (233). Similarly, a study in girls in Sonora, Mexico, indicates that it is possible that fetal, neonatal, or childhood exposure to contemporary pesticides can alter the pattern of breast development (208). The role of peripubertal EDC exposure on female breast development is less clear, but data from rodents show that mammary gland tissue is altered after acute, peripubertal exposure to DES, genistein, or DDT, with these EDCs acting as potent morphogens (234).…”
Section: Disruptions In Timing Of Pubertymentioning
confidence: 99%
“…En estudios con mujeres en edad reproductiva expuestas a DDT y sus metabolitos, se ha reportado daño genético medido a través del ensayo cometa en muestras de sangre (Yáñez et al 2004). Guillette et al (2006) reportaron un mayor crecimiento de senos, así como una baja relación entre el desarrollo de la glándula mamaria y tamaño del seno en jóvenes de zonas agrícolas del Valle del Yaqui, Sonora, comparadas con jóvenes de zonas serranas con menor exposición. Además, se encontró una asociación significativa entre la exposición a plaguicidas medido a través de la actividad AChE (< 20%) y un retraso en el crecimiento intrauterino (Levario-Carrillo et al 2004).…”
Section: Exposición En Mujeres En Edad Reproductivaunclassified
“…Upon further questioning, the mother shared that her own migrant worker mother toiled in the strawberry fields while pregnant with her, and that she herself grew up Bacross the street^from agricultural fields. An intriguing study of Yaqui women in Mexico found troubling anomalies in mammary growth in young girls growing up in a modern agricultural environment versus those from a nearby mountainous traditional ranching environment [73]. While the breasts of the girls appeared the same externally, upon palpation it was discovered that a significant number of those who dwelled in the farm lands had deficiencies in the volume of their glandular tissue.…”
Section: Mammary Hypoplasiamentioning
confidence: 99%